STRATEGI DIFERENSIASI PADA MADRASAH UNTUK MEMENANGKAN PERSAINGAN - Abdillah Mundir (JIE (Journal of Islamic Education), 2016)
In this globalisation and autotonomy region era, education havepurpose to industrialization process. The word of education can not beconsidered as sosial departement, but it must be proceed as industrywhich has to manage with professionalism. Due to firming up of acompetition, education departement will be left by the consument if itdoesn’t manage well. Differentiation strategy is strategythat give adifferent bergaining than given by competitor in a good service.Differentiation strategy supposed to school having a product orservicewith quality and function to differ with another competition islamiceducation school which have different character will master thecompetition continowly and always will have valuable customer whoseenjoy the valveof islamic education school.